KARAKTERISTIK STABILITAS DAN STABILITAS SISA CAMPURAN BETON ASPAL DAUR ULANG - Kasan, Muhammad (MEKTEK, 2009)
The aim of this research is to know characteristic of Marshall Stability and Marshall Immersion value of the old asphalt mixing that recycling by rejuvenating diesel oil. The old Asphalt mix from asphalt pavement deteroration on Jalan Soekarno Hatta, Palu Central Sulawesi.Result of extraction test of old asphalt mix was to found the asphalt content 4,6%. This scenarios of recycling asphalt in this research were five varieties of asphalt content and five varieties of rejuvenating agent. Varieties of asphalt content are 4,6% (without added of new asphalt), 5,1%, 5,6%, 6,1% and 6,6%. Varieties of rejuvenating agent are 0%, 5%, 10%, 15% and 20%. Specimen of asphalt pavement recycled testing by Marshall stability testing machine and volumetric analysis.The result of Marshall testing on Optimum Bitumen Content was found that increasing of rejuvenating agent content in asphalt recycling mix caused Marshall stability ,Marshall Immersion and Density Values were decrease. From Marshall stability value, maximum content of rejuvenating agent still required specification is 35,29% and from Marshall immersion value, maximum content of rejuvenating agent is 46,18%